Effect of AKT1 (p. E17K) Hotspot Mutation on Malignant Tumorigenesis and Prognosis - Chen, Ying; Huang, Lan; Dong, Yongjian; Tao, Changli; Zhang, Rongxin; Shao, Hongwei; Shen, Han (Frontiers in Cell and Developmental Biology, 2020)
The substitution of the seventeenth amino acid glutamate by lysine in the homologous structural domain of the Akt1 gene pleckstrin is a somatic cellular mutation found in breast, colorectal and ovarian cancers, named p. Glu17Lys or E17K. In recent years, a growing number of studies have suggested that this mutation may play a unique role in the development of tumors. In this review article, we describe how AKT1(E17K) mutations stimulate downstream signals that cause cells to emerge transformed; we explore the differential regulation and function of E17K in different physiological and pathological settings; and we also describe the phenomenon that E17K impedes tumor growth by interfering with growth-promoting and chemotherapy-resistant AKT1lowQCC generation, an intriguing finding that mutants may prolong tumor patient survival by activating feedback mechanisms and disrupting transcription. This review is intended to provide a better understanding of the role of AKT1(E17K) in cancer and to inform the development of AKT1(E17K)-based antitumor strategies.